Statistics for business and economics - Anderson, David R, 1941- (David Ray); Sweeney, Dennis J.; Williams, Thomas A.( 1944-) (Cincinnati: South Western-Thomson Learning, 2002)
This volume provides solid methodological development in the area of statistics for business & economics. The development of each technique is presented in an application setting with statistical results providing insights & solutions to problems.
Previous ed.: 1999.
Includes bibliographical references and index.
Keywords: Commercial statistics -- -- Methodology; Statistiek; Statistics; Economics -- -- Statistical methods